Pengaruh Experiential Marketing, Word Of Mouth Dan Kualitas Produk Terhadap Keputusan Pembelian Produk PT. Indako Trading Coy Medan - Ivan Steven Lie; Kelly Kelly; Fredy Fredy; Holfian Daulat Tambun Saribu; Rintan Br Saragih (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Indako Trading Coy was founded in 1966 and is located at Jalan Pemuda No 18 D-H Medan. PT. Indako Trading Coy has a Honda sales network consisting of 102 dealers, 191 AHASS workshops, and 414 spare parts stores spread across North Sumatra and Aceh. Currently, the company is experiencing a decline in consumer purchases, where the number of consumers making purchases each year is decreasing. Although the decline is not significant, if left unchecked, it could have a very negative impact. Based on observations made by the researcher through interviews with several consumers, it was found that there are various factors influencing the decrease in purchase decisions for the products offered by the company. Among these factors are experiential marketing, word of mouth, and product quality. The research population used in this study consists of all consumers who made purchases at the company during the 2023 period, totaling 3,043. The sampling technique used is Slovin’s formula, which resulted in 97 samples. The research findings indicate that Experiential Marketing has a positive and significant effect on Customer Satisfaction at PT. Indako Trading Coy Medan. Word of Mouth has a positive and significant effect on Customer Satisfaction at PT. Indako Trading Coy Medan. Product Quality has a positive and significant effect on Customer Satisfaction at PT. Indako Trading Coy Medan. Experiential Marketing, Word of Mouth, and Product Quality have a positive and significant effect on Purchase Decisions at PT. Indako Trading Coy Medan.